Sublimation and Its Control in the CRREL Permafrost Tunnel. - Johansen,N I; Chalich,P C; Wellen,E W (1981)
The U.S. Army Cold Regions Research and Engineering Laboratory's permafrost tunnel at Fox, near Fairbanks, Alaska, was used to investigate the sublimation process in permafrost silt. The rate of increase in thickness of the dried silt layer from sublimation was found to be approximately 0.023 in. (0.058 cm) in 1 month and closely related to the relative humidity in the tunnel. Sublimation prevention studies consisted of evaluation of various membranes to impede the sublimation. Ice was found to show promise as an easily installed, effective membrane when applied as a fine water mist and subsequently left to freeze. (Author)